Navigating a citizen science food waste project - Cody Gusto; Catherine Campbell; Kay Kelsey; Ziynet Boz (Journal of Agriculture, Food Systems, and Community Development, 2025)
While citizen science has increasingly gained recognition as a valuable approach for engaging the public in scientific research, the method has seen limited application in food waste contexts. Our reflective essay examines the application of citizen science to address household food waste as part of a broader, interdisciplinary research initiative, focusing on the challenges we experienced and the lessons we gleaned from applying the citizen science process to our research. Our study gathered two rounds of empirical household data on food and food-related packaging discard behaviors to refine a predictive agent-based model designed by our project partners to simulate household food waste patterns and implications. Over a two-week period in April 2024, citizen scientists in two Florida cities documented the types, quantities, and reasons for discarding food, as well as associated packaging waste. While the project demonstrated the utility of citizen science for gathering food waste data, it also highlighted several logistical and methodological challenges, including complexities in materials distribution, participant training, and maintaining data quality. Based on our experience, we offer recommendations for future citizen science projects in the food waste domain, emphasizing the importance of well-designed materials, robust partnerships, and strategies to mitigate participant fatigue. This essay underscores citizen science’s potential to illuminate consumer food waste research while offering guidance to researchers and practitioners interested in the method on how to mitigate challenges and achieve intended outcomes and impacts.